2022
DOI: 10.3390/fermentation8080366
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Biodegradation and Its Valorization

Abstract: Lignin, a rigid polymer composed of phenolic subunits with high molecular weight and complex structure, ranks behind only cellulose in the contribution to the biomass of plants. Therefore, lignin can be used as a new environmentally friendly resource for the industrial production of a variety of polymers, dyes and adhesives. Since laccase was found to be able to degrade lignin, increasing attention had been paid to the valorization of lignin. Research has mainly focused on the identification of lignin-degradin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 131 publications
0
7
0
Order By: Relevance
“…Although the molecular transformations resulting from CID fragmentation may be different than the ones triggered by enzymatically driven microbial processing, several studies have shown some interesting similarities in their pathways. For example, decarboxylation (CO 2 neutral loss during CID) has been recognized as a biodegradation mechanism of tannins and a fundamental reaction pathway of DOM photooxidation. , Moreover, demethoxylation pathways, correlated with CH 4 O neutral losses, have been previously reported during degradation of lignin, a potential DOM component. The absence of methoxy (CH 4 O loss)-based transformational processes in the common CHO structural families suggests that the mechanisms triggering the addition/subtraction of this functionality are characteristic to certain aquatic ecosystems. Examination of the neutral loss sequences among precursors in the families (data not shown) evidenced that at least one methoxy moiety was found in ∼50% of both SRFA and Pantanal structural families.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the molecular transformations resulting from CID fragmentation may be different than the ones triggered by enzymatically driven microbial processing, several studies have shown some interesting similarities in their pathways. For example, decarboxylation (CO 2 neutral loss during CID) has been recognized as a biodegradation mechanism of tannins and a fundamental reaction pathway of DOM photooxidation. , Moreover, demethoxylation pathways, correlated with CH 4 O neutral losses, have been previously reported during degradation of lignin, a potential DOM component. The absence of methoxy (CH 4 O loss)-based transformational processes in the common CHO structural families suggests that the mechanisms triggering the addition/subtraction of this functionality are characteristic to certain aquatic ecosystems. Examination of the neutral loss sequences among precursors in the families (data not shown) evidenced that at least one methoxy moiety was found in ∼50% of both SRFA and Pantanal structural families.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In contrast, lower abundance of this functionality was observed across HR-1 (<7%) and HR-5 (<3%) structural families, thus confirming the similarities between SRFA/Pantanal and HR-1/HR-5 pairs at the structural level. Interestingly, the replacement of methoxy functional groups with phenolic hydroxyl groups has been previously linked to biodegradation of highly methoxylated lignin. Therefore, transformation mechanisms involving methoxy moieties may be constrained in estuarine systems (HR-1/HR-5) due to extensive upstream lignin biodegradation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The American Society for Testing and Materials (ASTM) defines a plastic as compostable when it “undergoes degradation by biological processes during composting to yield carbon dioxide, water, inorganic compounds, and biomass at a rate consistent with other known compostable materials and that leaves no visible, distinguishable, or toxic residue.” This is a subgroup of biodegradable plastics, which are instead defined as “plastic in which the degradation results from the action of naturally-occurring micro-organisms such as bacteria, fungi, and algae.” Therefore, not all biodegradable plastics are compostable. Lignin is efficiently biodegraded by white-rot fungi and various types of bacteria, , but the degradation of lignin under composting conditions commonly used to dispose of food packaging items is incomplete and inefficient . Moreover, the properties introduced by the addition of lignin in a polymer matrix, such as improved gas barrier, decreased water permeability, and increased hydrophobicity, can reduce the material degradability in the composting conditions.…”
Section: Lignin In Food Packagingmentioning
confidence: 99%
“…Lignin, an aromatic polymer of LCB acts as a physical barrier in the process of polysaccharides extraction [1, 3,14]. It is degraded by a variety of ligninolytic enzymes such as laccases, versatile peroxidase manganese peroxidase, and lignin peroxidase [100]. Microorganisms (fungi and bacteria) are commonly used for the production of hydrolytic enzymes.…”
Section: Enzymatic Hydrolysis As An Integral Step In Biorefineriesmentioning
confidence: 99%
“…Microorganisms (fungi and bacteria) are commonly used for the production of hydrolytic enzymes. Micro-organisms such as Bacillus velezensis, Bacillus paranthracis, Aspergillus terreus, Aspergillus niger, Trametes versicolor, and Phanerochaete chrysosporium are few of the examples which produce enzymes with cellulolytic, hemicellulolytic, and ligninolytic capabilities [2,100]. Various factors such as enzymatic activity of saccharification enzymes, enzyme loading, substrate quantity, process conditions, and inhibitors present in the postpretreatment sugar hydrolysate [89].…”
Section: Enzymatic Hydrolysis As An Integral Step In Biorefineriesmentioning
confidence: 99%